PENDIDIKAN KARAKTER DALAM TINJAUAN PSIKOLOGI - Laurensius Arliman S (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The function of education is the transformation of culture and values to students, in order to be able to understand, internalize and convey to the next generation. One of them is character education. Of course character education will be very good if it is supported by other sciences. This article is supported by psychology. The research method used in this article is a literature review research method or literature study, which contains relevant theoretical theories. The conclusion of this article states that character education shapes a person's personality through character education, the results of which can be seen in one's real actions, namely good behavior, honest responsibility, respect for others, hard work, and so on. Character education is supported by educational psychology. Educational psychology is more of a science that can be applied in everyday life, especially on how our society manages learning. Educational Psychology develops into a science that focuses on the discovery and application of psychological principles and techniques into education, so the scope of educational psychology includes topics that are closely related to character education. Character education goals are very good to use and develop. Contents, methods in the form of implementation, methods in the form of guarding, educational tools in the form of action, environment for character education, and students, both to be used and developed which are supported by other sciences apart from psychology.